Possibilities of the Implementation of Foreign Experience of Value Policy in the Sphere of Interethnic Relations on Russian Conditions - VOLKOV, Yuriy G.; DENISOVA, Galina S.; LUBSKY, Anatoly V.; DEGTYAREV, Alexander K.; VOYTENKO, Valeriya P. (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017DO - 10.14505/jarle.v8.7(29).27, 2017)
Insufficient effectiveness of the administrative model of the national policy in Russian society implies a transition to new paradigmatic grounds for management practices in the field of interethnic relations, including taking into account the possibility of the implementation of foreign experience of value policy. The article reveals the difficulties, possibilities and prospects for the implementation of the experience of politics of values in the US and FRG in Russian conditions. It is concluded that value policy allows you to get rid of the administrative syndrome in Russian society, overcome the limitations of only the legal ʽmechanismsʽ for regulating inter-ethnic relations and move on to the communicative model of national politics.